2001
DOI: 10.1590/s1516-84842001000100003
|View full text |Cite
|
Sign up to set email alerts
|

Genotipagem do locus ABO (9q34.1) em doadores de sangue da região noroeste do Estado de São Paulo

Abstract: Os avanços da genética molecular permitiram o entendimento das bases moleculares do locus ABO. Considerando sua importância como marcador genético e suas aplicações, o objetivo deste estudo foi verificar a distribuição dos genótipos ABO em uma amostra da população brasileira oriunda da região noroeste do Estado ArtigoIntrodução O maior sistema de aloantígenos expressos nos eritrócitos e em outros tecidos humanos constitui-se de quatro fenótipos definidos pelas combinações de dois antígenos carboidratos A e B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
7
2
Order By: Relevance
“…On the other hand, previous studies in Southeast Brazil (Mattos et al, 2001) have shown lower O 1variant allele frequencies than those found in our sample, probably because the indigenous contribution in this region of country is the smallest. Along the same line, the frequency of the A phenotype reaches values around 35%, and the A allele frequency is more than 0.25 in these populations (Mattos et al, 2001), while in our sample of the North region the frequencies were 21.2 and 0.13%, respectively.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…On the other hand, previous studies in Southeast Brazil (Mattos et al, 2001) have shown lower O 1variant allele frequencies than those found in our sample, probably because the indigenous contribution in this region of country is the smallest. Along the same line, the frequency of the A phenotype reaches values around 35%, and the A allele frequency is more than 0.25 in these populations (Mattos et al, 2001), while in our sample of the North region the frequencies were 21.2 and 0.13%, respectively.…”
Section: Resultscontrasting
confidence: 99%
“…Comparing the Brazilian population data, our results show that O 1variant allele frequencies are lower than the frequencies reported for some Amerindians and higher than those for populations of Caucasian and African ancestry (Olsson et al, 1998), probably due to the influence of Portuguese colonization in the northern region of Brazil as well as the presence of Amerindians (Batista dos Santos et al, 1999). On the other hand, previous studies in Southeast Brazil (Mattos et al, 2001) have shown lower O 1variant allele frequencies than those found in our sample, probably because the indigenous contribution in this region of country is the smallest. Along the same line, the frequency of the A phenotype reaches values around 35%, and the A allele frequency is more than 0.25 in these populations (Mattos et al, 2001), while in our sample of the North region the frequencies were 21.2 and 0.13%, respectively.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Since screening for T. gondii antibodies and ABO blood group system phenotyping are compulsory for pregnant women in Brazil, we assembled data from the medical records of women who gave birth in our hospital. The background of the series concerning ethnicity, age and ABO blood groups is representative of the geographic area in which the study was carried out (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…3 Recently, Mattos et al demonstrated that the ABO blood groups among Brazilians are highly polymorphic when analyzed by molecular methods. 4 Among the first epidemiological studies to establish associations between blood groups and diseases, there were some demonstrations of high frequencies of the O blood group and non-secretor phenotype of ABH antigens among patients suffering from peptic ulcers. 5,6 It was later shown that the Helicobacter pylori bacillus is the main etiologic agent associated with gastric ulceration, being present in more than 80% of patients with this disease.…”
Section: Introductionmentioning
confidence: 99%